Prairies Thrive Where Row Crops Drown: A Comparison of Yields in Upland and Lowland Topographies in the Upper Midwest US - Adam C. von Haden; Mathew E. Dornbush (Agronomy, 2016)
Cellulosic biofuel production is expected to increase in the US, and the targeted establishment of biofuel agriculture in marginal lands would reduce competition between biofuels and food crops. While poorly drained, seasonally saturated lowland landscape positions are marginal for production of row crops and switchgrass (Panicum virgatum L.), it is unclear whether species-diverse tallgrass prairie yield would suffer similarly in saturated lowlands. Prairie yields typically increase as graminoids become more dominant, but it is uncertain whether this trend is due to greater aboveground net primary productivity (ANPP) or higher harvest efficiency in graminoids compared to forbs. Belowground biomass, a factor that is important to ecosystem service provisioning, is reduced when switchgrass is grown in saturated lowlands, but it is not known whether the same is true in species-diverse prairie. Our objectives were to assess the effect of topography on yields and live belowground biomass in row crops and prairie, and to determine the mechanisms by which relative graminoid abundance influences tallgrass prairie yield. We measured yield, harvest efficiency, and live belowground biomass in upland and lowland landscape positions within maize silage (Zea mays L.), winter wheat (Triticum aestivum L.), and restored tallgrass prairie. Maize and winter wheat yields were reduced by more than 60% in poorly drained lowlands relative to well-drained uplands, but diverse prairie yields were equivalent in both topographic settings. Prairie yields increased by approximately 45% as the relative abundance of graminoids increased from 5% to 95%. However, this trend was due to higher harvest efficiency of graminoids rather than greater ANPP compared to forbs. In both row crops and prairie, live belowground biomass was similar between upland and lowland locations, indicating consistent biomass nutrient sequestration potential and soil organic matter inputs between topographic positions. While poorly drained, lowland landscape positions are marginal lands for row crops, they appear prime for the cultivation of species-diverse tallgrass prairie for cellulosic biofuel.